2005
DOI: 10.7249/tr333
|View full text |Cite
|
Sign up to set email alerts
|

Police-Community Relations in Cincinnati

Abstract: The RAND Corporation is a nonprofit research organization providing objective analysis and effective solutions that address the challenges facing the public and private sectors around the world. RAND's publications do not necessarily reflect the opinions of its research clients and sponsors. R ® is a registered trademark. © Copyright 2005 City of CincinnatiAll rights reserved. No part of this book may be reproduced in any form by any electronic or mechanical means (including photocopying, recording, or informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…These results are largely consistent with the findings in our earlier reports (Riley et al, 2005;Ridgeway et al, 2006;Schell et al, 2007). As noted in earlier reports, these findings cannot answer whether racial bias does or does not exist, but they do help explain why black Cincinnati residents perceive that it does, which may lead to a more negative attitude in future interactions with the police.…”
Section: Summary XXVIIsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are largely consistent with the findings in our earlier reports (Riley et al, 2005;Ridgeway et al, 2006;Schell et al, 2007). As noted in earlier reports, these findings cannot answer whether racial bias does or does not exist, but they do help explain why black Cincinnati residents perceive that it does, which may lead to a more negative attitude in future interactions with the police.…”
Section: Summary XXVIIsupporting
confidence: 91%
“…The finalized set of measures and coding instructions, a codebook, was developed after a review of the study goals, an intensive review of the scientific literature, and an empirical examination of the content that could be discerned from the recordings. A fuller discussion of the development of these instruments is contained in the year 1 report (Riley et al, 2005). The actual content and quality of the recordings presented real limitations on what measures could be reliably extracted from these interactions.…”
Section: Coding Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The year-one 1 report (Riley et al, 2005) reported on all of the tasks under the contract's initial year. Those tasks were to analyze Cincinnati crime and staff deployment patterns to survey the community on its satisfaction with police services to analyze motorist stop data to analyze audio and video records from motorist stops to assess CPD staffing patterns to assess CPD problem-solving processes to survey citizens who have interacted with the police to survey officers and citizens involved in complaints to survey officers to obtain their opinions about their work and the community.…”
Section: Evaluation Of Progress Toward the Collaborative Agreement's mentioning
confidence: 99%
“…It has also been suggested that where these types of multi-agency partnerships utilise community panels, there may be problems linked to the selection of voluntary community members as well as the capacity of these members to mobilise, represent and report back to their constituencies (Barnes 2008). Riley et al (2005) found that while practices and the ability to gain influence varied, formal panels where voluntary and community representatives were trained in problem-oriented policing (POP) technologies had the most likelihood of gaining community influence.…”
Section: The Community Meeting As a Practice Of Co-governancementioning
confidence: 99%